Alleviating of Lead toxicity using salicylic acid foliar spray in common bean (Phaseolus vulgaris L.) plant - Halalal R. Qader; Karim Salih Abdul (Zanco Journal of Pure and Applied Sciences, 2020)
This study was carried out in a greenhouse at the college of science university of salahaddin,erbil, Iraq. Salicylic acid (SA) and Lead (pb) with (0, 50, 100, 200 and 400 ppm) and pb (0, 5 and 10 ppm) are used in a (type of the experiment must be recorded) experiment. Consisting of 10 treatment combinations with 4 replicates. Treatments were compared according to Duncan’s multiple range tests at 0.05 level. Some vegetative growth, yield and chemical components were measured. The results notices that SA significantly decreased the harmful effects of Pb on the vegetative growth characteristics such as height of plant number of leaves, number of branches, weight dry of shoot system, also on yield parameters such as number of seeds per pod, dry weight of 100 seeds and on chemical contents such as chlorophyll a and total chlorophyll contents, total protein content of leaves and total sodium.